Legal Perspectives on Religious Conflict Resolution Among Youth: A Study of Youth Community Strategies for Fostering Interfaith Harmony - Iman Fadhilah; Nur Rois; Imam Khoirul Ulumuddin; Aris Abdul Ghoni; Ubbadul Adzkiya’; Nur Izzati binti Ab Ghani (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement) JPHI, 2025)
This research aims to identify and analyse the strategies used by youth communities in Central Java in resolving religious conflicts and maintaining interfaith harmony. The main research question posed is how the strategies of youth communities in Central Java respond to and resolve religious conflicts in order to maintain social harmony. This research uses a qualitative approach with a case study design, involving in-depth interviews, participatory observation, and documentation of several interfaith youth communities in major cities in Central Java such as Semarang, Solo, and Yogyakarta. The results showed that the youth community developed conflict resolution strategies based on interfaith dialog, cultural approaches, and strengthening diversity literacy through social media and informal education. These strategies have proven effective in building collective consciousness, strengthening social solidarity and creating safe spaces for interfaith interaction at the grassroots level.